Pengaruh hidroterapi rendam kaki air hangat terhadap kekuatan otot pada pasien stroke non hemoragik - Setiyawan Setiyawan; Lina Pratiwi; Noerma Shovie Rizqiea (Poltekkes Kemenkes Yogyakarta, 2019)
Non-hemorrhagic stroke is a disease which is related to a functional disorder of the brain due to the blood vessel blockage by a blood clot, or by the narrowing of an artery or some arteries that lead to the brain which causes weakness of muscular strength. One of the non-pharmacological therapies, which are beneficial to non-hemorrhagic stroke patients, is hydrotherapy. Hydrotherapy is a therapy which utilizes water to cure or relieve various complaints. One of which is the complaint of how to strengthen muscular strength. The objective of this research is to investigate the effect of warm footbath hydrotherapy to increase the muscular strength of non-hemorrhagic stroke patients. This research used the quasi-experimental research method ith pre-test and post-test nonequivalent control group design. Non-probability sampling with purposive sampling was used to determine its samples. The samples consisted of 40 respondents, into two groups: intervention and control group. The data of the research were analyzed by using the Wilcoxon’s Test and Mann Whitney’s Test. The result of the research shows that the footbath hydrotherapy had an effect on the muscular strength of the non-hemorrhagic stroke patients as indicated by the p-value = 0.000, and there was a difference between the control group and the intervention group where the p-value was 0. 008. The footbath hydrotherapy affected the muscular strength of non-hemorrhagic stroke patients. Thus, nurses as health practitioners are expected to administer warm footbath hydrotherapy to increase the muscular strength of non-hemorrhagic stroke patients.